New insights on hyperglycemia in 17-hydroxylase/17,20-lyase deficiency - Xu, Lingling; Lu, Lin; Tong, Anli; Chen, Shi; Li, Wei; Zhang, Huabing; Ping, Fan; Li, Yuxiu (Frontiers in Endocrinology, 2022)
Objective The adrenal glands of patients with 17-hydroxylase/17,20-lyase deficiency (17OHD) synthesize excessive 11-deoxycorticosterone(DOC) and progesterone, and produce less amount of sex steroid production. Mineralocorticoids and sex hormones play an important role in regulating glucose homeostasis. This study aimed to describe the glucose metabolism in 17OHD patients diagnosed at Peking Union Medical College Hospital (PUMCH). Design/methods A total of 69 patients diagnosed with 17OHD after adolescence in PUMCH from 1995 to June in 2021. Among them 23 patients underwent a 3-hours oral glucose tolerance test (3hOGTT) after being diagnosed with 17OHD. Insulin response in patients with normal glucose tolerance (NGT) were further compared between the study two groups with different kalemia status. Another 19 patients were followed up to 30 years and older. All clinical data were obtained from the hospital information system of PUMCH. Results Baseline: (1) The average body mass index(BMI) of all patients at baseline was 20.3±3.7kg/m2. Twenty-three patients underwent 3hOGTT, of whom three were diagnosed with diabetes mellitus, and one with impaired glucose tolerance (IGT). Positive correlation between the ratio of progesterone to upper limit of normal range (P times) and hyperglycaemia was exist(r=0.707, P=0.005). (2) In 19 NGT patients, the insulin concentrations at 0 minute, results of the homeostasis model assessment for β-cell function and insulin resistance were lower in the hypokalaemia group than in the normal kalemia group(7.0(5.8-13.2) vs 12.4(8.9-14.9) μIU/ml, P=0.017; 115.5(88.2-240.9) vs 253.1(177.2-305.8), P=0.048; 1.54(1.17-2.61) vs 2.47(1.91-2.98), P=0.022, respectively). Follow-up: Four patients had IGT, while seven patients had diabetes mellitus. Of the 19 patients ,11 had hyperglycaemia. P times was significantly higher(7.6(5.0-11.0) vs 3.75(2.2-5.3), P=0.008) in hyperglycemia group than in the normal glucose group. Conclusions Abnormal glucose metabolism was common in 17OHD patients, which was possibly associated with hypokalaemia and high progesterone levels. Routine monitoring on glucose metabolism in 17OHD patient should be conducted.